Cytotoxic effect of biosurfactant produced by Lactobacillus acidophilus and study its synergistic effect with certain antibiotics against S. aureus and E. coli (Eurasian Medical Research Periodical, 2022)
The aim of this research was to extract a significant amount of biosurfactant on an industrial scale from a local isolation of Lactobacillus acidophillus. This assignment was assigned to a 7L laboratory bioreactor, and all production parameters were established using batch culture experiments. At 30oC and 6.5 pH, a bioreactor with a working volume of 3.5 L was run for 120 hours to achieve 32 g/L. The manufacturing medium's supernatant was employed to lower water's surface tension from 72 to 24 mN/m, resulting in a 57 percent emulsification activity. The product was extracted with a variety of solvents and purified on a silica gel column (3.5 x 30cm) using glass chromatography. The toxicity of BS against breast cancer (AMJ-13) cell line was found to be 23%. When BS was used with antibiotics to treat pathogenic clinical isolates, it was discovered that ampicillin and tetracycline have a synergistic effect against S. aureus and E. coli.